Pengaruh Model Pembelajaran Quantum Learning Dengan Media Piranti Lunak Presentasi Terhadap Hasil Belajar Pada Materi Perkalian Bilangan Bulat Di Kelas V SDN 5 Simpangkatis - Yessy Andiani; Vika Martahayu; Ayen Arsisari (Jurnal Inovasi Matematika, 2019)
This research axamines about the influence of Quantum Learning model with presentation software media to studentsâ€™ achievement on the integer multiplicationmaterial for the fifth grade at SD Negeri 5 Simpangkatis, which the purpose to determine whether or not the influence of Quantum Learning model with presentation software media to studentsâ€™ achievement in integer multiplication material for the fifth grade at SD Negeri 5 Simpangkatis. This research was conducted in class V at SD Negeri 5 Simpangkatis in Academic Year 2018/2019.This research uses a quantitative approach with the â€œPre Experimental designâ€ method, and uses the design of One-Group Pretest-Posttes Design. The sampling technique in this research used purposive sampling. The population in this research were all students of fifth grade, while the sample of this research amounted to 24 students. The data collection techniques used in the form of tests consisting of 5 questions. The prerequisite test used is the Lillifors test in order to test the normality of the data. Based on the result of the Lillifors test it was found that the data were normally distributed. Based on the analysis of hypothesis test from the results of the T-test calculation with tcount>ttabel (18,06>2,05), it can be interpreted that Ha is accepted. So the result of this research show that there is a positive influence on the Quantum Learning model with presentation media to studentsâ€™ achievement on the integer multiplicationmaterial for the fifth grade at SD Negeri 5 Simpangkatis.